2023
DOI: 10.1002/aenm.202204218
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Vertically Aligned Inorganic‐Polymer Nanocomposites with Abundant Lewis Acid Sites for Ultra‐Stable Solid‐State Lithium Metal Batteries

Abstract: Nanocomposite solid polymer electrolytes are considered as a promising strategy for solid‐state lithium metal batteries (SSLMBs). However, the randomly dispersed fillers in the polymer matrix with limited Li+ transference number and insufficient ionic conductivity severely sacrifice the ion transport capacity, thus restricting their practical application. To tackle these issues, a magnetic field‐assisted alignment strategy is proposed to disperse the vertically aligned akaganéite nanotube in the polymer matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…The introduction of defect sites, such as oxygen vacancies, on inorganic fillers has been shown to regulate the local environment of Li + ions and decrease the activation energy for Li + ion transport. 128 Recently, Goodenough et al 129 investigated the local environments of Li + ions in SPEs. By introducing fillers with oxygen vacancies, which effectively enhanced the migration of Li + ions, they observed that the interactions between Li + ions and oxygen atoms in PEO were decreased compared to the interactions in the absence of fillers, proving that oxygen vacancies of fillers indeed can greatly enhance the migration of Li + ions.…”
Section: Mechanical Performance Of Spesmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of defect sites, such as oxygen vacancies, on inorganic fillers has been shown to regulate the local environment of Li + ions and decrease the activation energy for Li + ion transport. 128 Recently, Goodenough et al 129 investigated the local environments of Li + ions in SPEs. By introducing fillers with oxygen vacancies, which effectively enhanced the migration of Li + ions, they observed that the interactions between Li + ions and oxygen atoms in PEO were decreased compared to the interactions in the absence of fillers, proving that oxygen vacancies of fillers indeed can greatly enhance the migration of Li + ions.…”
Section: Mechanical Performance Of Spesmentioning
confidence: 99%
“…The introduction of defect sites, such as oxygen vacancies, on inorganic fillers has been shown to regulate the local environment of Li + ions and decrease the activation energy for Li + ion transport. 128 Recently, Goodenough et al . 129 investigated the local environments of Li + ions in SPEs.…”
Section: Molecular-level Designs Of Spesmentioning
confidence: 99%
“…19,20 Wang et al 21 discovered that the incorporation of succinonitrile as a plasticizer effectively diminishes the crystallinity of PEO and can enable rapid Li + Following the above strategy, incorporating both positive and negative charge groups (CGs) into PEO-based SPEs to achieve the desired properties can also greatly enhance their ion conduction properties. For instance, Nie et al 22 utilized vertically aligned β-FeOOH fillers in the electrolyte. This configuration allows the anions to be captured by Fe 3+ ions, while the Li + transport was facilitated by the abundant hydroxyl groups on β-FeOOH's surface.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[20][21][22] In contrast, PEs based on polymer network have better mechanical flexibility, processability, and interfacial compatibility with electrode, and have distinctive advantages in the field of high-performance SSEs. [23,24] Among PEs, the ionic conductivity of gel polymer electrolytes (GPEs) can be comparable to liquid electrolytes, and the existence of the polymer network can effectively avoid the leakage of liquid components. [25,26] More importantly, the in situ constructed GPEs further enhance the interface compatibility, realizing the balance between safety, interface contact, and ionic conductivity.…”
Section: Introductionmentioning
confidence: 99%